Aktivitas fosfatase dan produksi asam organik di rhizosfer dan hifosfer bibit kelapa sawit bermikoriza *) Phosphatase activity and organic acid production in rhizosphere and hyphosphere of mycorrhizal oil palm seedling - Happy WIDIASTUTI; Nampiah SUKARNO; Latifah Kosim DARUSMAN; Didiek Hadjar GOENADI; Sally SMITH; Edi GUHARDJA (Menara Perkebunan, 2003)
SummaryStudies on the mechanism of the higher Puptake of oil palm seedling colonized witharbuscular mycorrhizal fungi throughsolubilizing of fixed P by organic acid orhydrolysis of organic P by phosphatase activityhave not been reported yet. This experiment wasaimed to examine the phosphatase activity andproduction of organic acids in rhizosphere andhyphosphere, mycorrhizal and non-mycorrhizaloil palm seedling. Oil palm seedling were grownfor 26 weeks in sterilized Cikopomayak acid soilin 20.5 cm diameter pots with three compart-ments, a central one for root growth(rhizosphere) and two adjacent on both side nextto the root compartment for hyphal growth(hyphosphere). Compartmentation was accom-plished by a 0.25 mm stainless steel filter. Allcompartment received a uniform concentration ofphosphorus (300 P mg kg -1 soil) either in organic(Na-phytate) or inorganic NH 4 HPO 4 form.Acaulospora tuberculata inoculum was establish-ed in pot culture using Pueraria phaseoloides as ahost, while Gigaspora margarita was propagatedusing maize as a host. AM fungal inoculumapplied as mixed propagules in optimum dosage.The experiment was conducted to asses ninetreatments combination between AM inoculation(without, A. tuberculata, and G. margarita) andsources of P (without P, inorganic P NH 4 HPO 4 ,and organic P Na phytate). Factorial in completerandomized design with two factors and threereplications was used in this research. In thehyphal compartment acid phosphatase activitywas much higher than alkaline phosphataseactivity, while in the rhizosphere alkalinephosphatase activity was higher compared toacid phosphatase activity. Acid phosphataseactivity in rhizosphere of oil palm seedlingsinoculated with A. tuberculata was significantlyhigher compared to uninoculated seedlings.However, both acid phosphatase activity andalkaline phosphatase activity were slightlyenhanced by mycorrhizal inoculation. In contrast,organic acid production between inoculatedseedling and uninoculated seedling was notsignificantly different. It seems that AM fungalsymbiosis with oil palm enhance mineralizationof organic P in spite of solubilization ofinorganic P.RingkasanMekanisme peningkatan pertumbuhankelapa sawit bermikoriza khususnya yangdisebabkan aktivitas pelarutan P anorganik yangterfiksasi melalui pelarutan oleh asam organikatau hidrolisis P organik oleh aktivitas fosfataseelum dilaporkan. Percobaan ini bertujuanmenetapkan aktivitas fosfatase dan produksi asamorganik di rhizosfer dan hifosfer, bibit kelapasawit bermikoriza dan tidak bermikoriza. Kelapasawit ditumbuhkan selama 26 minggu pada tanahmasam Cikopomnayak steril pada pot ber-diameter 20,5 cm yang terbagi atas tiga daerah,ruang tengah untuk pertumbuhan akar (rhizosfer)dan dua daerah di sebelahnya untuk pertumbuhanhifa (hifosfer). Penyekatan pot menggunakanfilter stainless steel berukuran lubang 0,25 mm.Semua daerah dipupuk P pada konsentrasi300 P mg kg -1 tanah baik dalam bentuk organik(Na-phytate) maupun anorganik (NH 4 HPO 4 )Inokulum CMA merupakan hasil perbanyakandengan sistem kultur pot menggunakan inangPueraria phaseoloides untuk Acaulosporatuberculata sedangkan untuk Gigasporamargarita menggunakan inang jagung. InokulumCMA berupa propagul campuran pada dosisoptimum. Percobaan dilakukan untuk mengujisembilan perlakuan yang merupakan kombinasiantara inokulasi CMA (tanpa, A. tuberculata,dan G. margarita) dan sumber P (tanpa P,anorganik P NH 4 HPO 4 , dan organik P Naphytate). Rancangan percobaan ialah rancanganacak lengkap faktorial dengan tiga ulangan untukmasing-masing perlakuan. Di hifosfer aktivitasfosfatase asam lebih tinggi daripada fosfatasealkalin, sedangkan di rhizosfer aktivitas fosfatasealkalin lebih tinggi dibandingkan dengan aktivitasfosfatase asam. Aktivitas fosfatase asam dirhizosfer bibit kelapa sawit yang diinokulasi A.tuberculata nyata lebih tinggi dibandingkandengan bibit yang tidak diinokulasi. Aktivitasfosfatase asam dan fosfatase alkalin sedikit lebihtinggi dengan inokulasi CMA. Sebaliknya,produksi asam organik antara bibit yangdiinokulasi dan bibit yang tidak diinokulasi tidakberbeda nyata. Tampak bahwa simbiosis CMAdengan kelapa sawit lebih meningkatkanmineralisasi P organik dan kurang meningkatkanpelarutan P anorganik.